Dimensi Spiritual dalam Proses Penciptaan dan Perkembangan Manusia: Studi Analisis Atas Tafsir Fī Zilāl Al-Qur’ān Karya Sayyid Qutb - Ulfah, Mailani Ulfah; Zakiy, Ahmad Zakiy (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2024)
The study of the relationship between science and the Qur’an gave birth to new developments in the world of Qur’anic interpretation. This was marked by the rise of several interpretations of scholars who tried to adjust scientific discoveries with the information of the Qur’an. But in the midst of the development of these studies, there are some scholars who are reluctant to link scientific issues with the description of the content of the Qur’an. One of them is Sayyid Qut}b. This study aims to examine Sayyid Qut}b’s interpretation of QS. al-Mu’minūn [23]:12-14 which contains a description of the process of creation and human development. The type of research used is a type of literature study research with an analytical descriptive research model. The results of this study show, first, Qut}b’s initial discussion of this verse provides information that the regularity of the process of creation and human growth shows evidence of a deliberate creation, so that the information of some scientists of the absence of a creator is very unfounded. Secondly, in the explanation of verse 12 there is a tendency of Qut}b not to link the Qur’anic information with scientific theories. Third, the sentence “We will make him a different creature” in verse 14 indicates a hint of the spirit that makes humans a creature that has distinctive character that is very much different from other creatures such as animals. In the end, Quṭb’s descriptions in his tafsir look thick with spiritual and theological nuances. Although this verse basically contains kawniyyah signs, Qut}b seems to lead it to spiritual aspects to provide awareness of Allah’s omnipotence in the aspect of human creation.